Fault tolerant positioning using WLAN signal strength fingerprints - Laoudias, C.; Panayiotou, C. G.; Michaelides, Michalis P. (My University, 2010)
Accurate and reliable location estimates using wireless networks are important for enabling indoor location oriented services and applications, such as in-building guidance and asset tracking. Providing adequate level of accuracy in case of faults or attacks to the positioning system is equally significant, thus our main interest is on the fault tolerance of positioning methods, rather than the absolute accuracy in the fault-free case. We introduce several fault models to capture the effect of failures in the wireless infrastructure or malicious attacks and discuss how these models can simulate the corruption of signal strength values during positioning. The models are used to investigate the fault tolerance of positioning methods and evaluate them in terms of their performance degradation as the percentage of corrupted signal strength measurements increases. Experimental results using our fault models are also presented. © IEEE.
Keywords: Fault tolerance; Fault tolerant systems; Wireless LAN; Data models; Accuracy; Artificial neural networks; Measurement